Neurological Outcomes following Iatrogenic Vascular Injury during Posterior Atlanto-axial Instrumented Fusion. Issue 1 (April 2016) - Ahmad, Faiz; Akinduro, Oluwaseun; Baum, Griffin; Howard, Brian; Pradilla, Gustavo; Grossberg, Jonathan; Rodts, Gerald
Introduction: Iatrogenic vascular injury is a feared complication of posterior atlanto-axial instrumented fusion. A better understanding of clinical course following this injury will allow surgeons to better care for these patients. The object of the study was to systematically review the neurologic outcomes after iatrogenic vascular injury during atlanto-axial posterior instrumented fusion. Methods: A systematic review of the PubMed database was performed, following the guidelines outlined in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The extracted data was recorded in an excel spreadsheet. To be included, the patients must have undergone fusion of the C1/C2 joint using posterior instrumentation with injury to an arterial vessel directly attributable to the surgical procedure. Results: 86 incidences of vascular injury were found in 41 articles with 11200 patients. The average age of included patients was 46.4 +/− 24.1 for the screw rod construct (SRC) group and 36.2 +/− 28.2 for the transarticular screw (TAS) group. Vascular injury in SRC cases resulted in ipsilateral stroke in 15.9% ( n  = 7/44) of patients and neurologic deficit in 22.7% ( n  = 10/44) of patients with a permanent neurologic deficit occurring in 11.4% ( n  = 5/44) of patients. Vascular injury following TAS fixation resulted in ipsilateral stroke in 11.9% of cases ( n  = 5/42) and neurologic deficit in 23.8% of cases with the deficit being permanent in 9.5% ( n  = 4/42) of cases. Death was the result of injury in 9.1% ( n  = 4/44) of SRC cases and 7.1% ( n  = 3/42) of TAS cases. Conclusions: Neurological morbidity after iatrogenic vascular injury during posterior C1/2 fixation is higher than previously reported in literature. There has been no large-volume studies aimed at identifying a rate of neurologic complications after iatrogenic injury. Surgeons should be aware of the normal and anomalous vertebral artery anatomy to avoid this potentially catastrophic injury.